A Comparative Study of Nutrients, Cadmium, and Chromium Bioremoval Efficiencies of Three Emergent Macrophytes From a Metal‐Contaminated Wastewater. Issue 11 (26th October 2015) - Kouki, Soulwène; Saidi, Neila; M'hiri, Fadhel; Hafiane, Amor
Abstract : A comparative study of the metal tolerance and removal capacities of three emergent macrophyte species was established in an artificially contaminated wastewater. The removal efficiencies of chromium (Cr), cadmium (Cd), ammoniacal‐nitrogen (NH4 ‐N), nitrate‐nitrogen (NO3 ‐N), and ortho ‐phosphate (PO4 ‐P) by mono‐cultures of Arundo donax, Phragmites communis, and Typha latifolia were determined. The leaf number as well as Cr‐ and Cd‐plant tissue contents were assessed after 15 days of exposure to metal concentration gradients. Arundo donax achieved the highest removal efficiencies of NH4 ‐N (72%) and PO4 ‐P (83%). However, P. communis and T. latifolia accomplished significantly higher reduction rates of NO3 ‐N (86 and 82%, respectively). With exposure to the wastewater metal contamination, A. donax was more resistant than the other two species and produced the highest leaf number for both pollutants Cr (13 leaves at 20 mg Cr/L) and Cd (14 leaves at 2 ppm). In addition, compared to P. communis and T. latifolia, A. donax showed significantly higher accumulative capacities for Cr and Cd in terms of dry weight (DW) of the plant biomass in both belowground (16.9 mg Cr/kg DW, 189 μg Cd/kg DW) and aboveground (10.1 mg Cr/kg DW, 130 μg Cd/kg DW) parts. Abstract : Arundo donax, Phragmites communis, and Typha latifolia are considered as potential macrophytes for wastewater treatment. A comparative study of metals uptake and nutrients removal capacities of the three species from a metal‐contaminated wastewater allows concluding the highest levels of removal of NH4 ‐N and PO4 ‐P, tolerance to metals, and uptake of Cr and Cd achieved by A. donax .